Modelagem matemática: uma metodologia alternativa de ensino - Abdanur, Patricia (2006)
This term paper proposes to argue and to analyze aspects of the Mathematical Modeling in the scope of the Mathematical Education, the teaching and learning of the Mathematics in the Basic Education s context. It presents as its central objective the analysis of the Mathematical Modeling while a differentiated educative practice for the teaching and as an investigation s leading question it seeks to identify the favored aspects of the Modeling whereas a practice that comes from the group or student s interest? By hypothesis, the disinterest for the taught subject in Mathematics provokes a deficient learning in the student s. The paper presents a general view of Mathematical Education and its perspectives for the teaching in the Basic Education facing the National Guidelines for the Elementary and High School system. It approaches the Modeling since the Pre-history until the Contemporary Age. For the central objective s achievement and other elect objectives of this investigation, it was used the explorative researches to provide a greater familiarity with the subjects that treats the Mathematical Education and Modeling. Furthermore, to become aware about the initial works characteristics of descriptive research. To get the knowledge about these initial works with the Modeling, it was used material produced by the first experiences participators in the specialization courses which were carried through in 1983/1984. It consists in the quantity of Education Laboratory of Education and Mathematical Education research LEPEM . It presents and analyzes the lived experiences with Modeling (in a public and in a private school), trying to identify aspects that constitute it as a differentiated practice developing and following the steps considered by Burak (1998/2004). The results of the experiences point to new teaching perspectives of the Mathematical Education. Word-Keys: Teaching and Learning, Modeling Mathematics, Mathematical Education, Interdisciplinary, Contextualization